Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s11356-014-2693-2
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of reducing greenhouse gas emissions and air pollution through energy sources: evidence from a panel of developed countries

Abstract: The objective of the study is to investigate the long-run relationship between climatic factors (i.e., greenhouse gas emissions, agricultural methane emissions, and industrial nitrous oxide emission), air pollution (i.e., carbon dioxide emissions), and energy sources (i.e., nuclear energy; oil, gas, and coal energy; and fossil fuel energy) in the panel of 35 developed countries (including EU-15, new EU member states, G-7, and other countries) over a period of 1975-2012. In order to achieve this objective, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…These results are consistent with the previous studies of Akhmat et al [67], Zeb et al [68], Arouri et al [69], Narayan and Smyth [70], Weisz et al (2006) and Khan et al [71] in the sense that these studies confirmed the long-run and causal relationship between energy and growth across the World.…”
Section: Resultssupporting
confidence: 93%
“…These results are consistent with the previous studies of Akhmat et al [67], Zeb et al [68], Arouri et al [69], Narayan and Smyth [70], Weisz et al (2006) and Khan et al [71] in the sense that these studies confirmed the long-run and causal relationship between energy and growth across the World.…”
Section: Resultssupporting
confidence: 93%
“…Akhmat et al (2014a) investigated the air pollution, GHG emissions and low birth weight in Pakistan and found that carbon emissions have a greater impact in order to influence low birth weight babies as compared to GHG emissions in a country. Akhmat et al (2014b) further argued that GHG emissions may be reduced by adopting the nuclear energy consumption in countries energy portfolios; however, for different air pollutants, nuclear energy should be consumed at caution with care. Zeb et al (2014) examined the socioeconomic and environmental factors in SAARC countries and found differential causal connections between energy demand, CO 2 emissions, economic growth, livelihoods and resource depletion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chinese stainless steel companies should develop clean technologies such as waste heat recovery through exhaust gas recirculation and update obsolete and low‐efficiency equipment to reduce energy consumption . Coal is inexpensive and abundant, and therefore it is a reliable energy source for stainless steel manufacturing plants.…”
Section: Resultsmentioning
confidence: 99%